A New Boundary Condition for the Three-Dimensional MHD Equation and the Vanishing Viscosity Limit. (Journal of Partial Differential Equations, 2017)
In this paper, we consider the viscous incompressible magnetohydrodynamic (MHD) system with a new boundary condition for a general smooth domain in $\mathbb{R}$3. We obtain the well-posedness of the system and the vanishing viscosity limit result.
Keywords: Incompressible MHD system; a new boundary condition; the general smooth domain; vanishing viscosity limit